Peranan Sekolah dalam Upaya Pencegahan Penyalahgunaan Narkoba di Kalangan Pelajar - Daulat Nathanael Banjarnahor; Firinta Togatorop; Doris Yolanda Saragih (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The drugs problem in Indonesia is still complex and urgent. This is important because, in the last 10 years, this drug problem has been rife and has become news in various media so it has become widespread. Evidence that can be seen together is the continued increase in the number of drug abusers or addicts significantly, accompanied by an increase in the number of disclosures of drug crime cases, which have increasingly varied patterns and the larger and more complex the networks or syndicates. Drug trafficking has spread to many groups, ranging from adults, teenagers, students, and even children. The purpose of carrying out Community Service Activities is to build an introduction and understanding of the types and dangers of drugs and what role schools can play in preventing drug abuse among students. PkM activities are carried out for 1 day, namely on Wednesday 12 July 2023, and are carried out using the method of raising awareness or increasing understanding of a problem in the form of activities in the form of counseling or material lectures aimed at students and the school with the title "The Role of Schools in Efforts Prevention of Drug Abuse among Students". The counseling or lecture method interspersed with discussions was chosen by the team as the most effective method for introducing and strengthening understanding of the dangers of drugs to school officials and students. Narkoba is an abbreviation of Narcotics, Psychotropics, and Addictive Materials. In various kinds of literature, it is explained that the notion of narcotics is a substance/substance that can affect a person's psychological/psychological condition (thoughts, feelings, and behavior) and can cause physical and psychological dependence. Regarding the role of the school in efforts to prevent drug abuse among students, it is divided into two forms, namely the role of the school (the school) and the role of students who can collaborate with the school.